2007
DOI: 10.1007/s10530-007-9173-2
|View full text |Cite
|
Sign up to set email alerts
|

Displacement in two invasive species of leafminer fly in different localities

Abstract: Liriomyza sativae was displaced by L. trifolii in the USA probably due to the lower insecticide susceptibility of L. trifolii, but L. trifolii was displaced by L. sativae in Japan. To know the possible causes of the species displacement observed in Japan, differences in the insecticide susceptibility, fecundity, effects of natural enemies, and reproductive interference between L. trifolii and L. sativae were evaluated. As a result, the higher fecundity of L. sativae and differential effects of parasitoids on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 17 publications
2
28
0
2
Order By: Relevance
“…Differential host plant use and differential effects of natural enemies have been suggested as contributing factors to displacement among Liriomyza species in the United States (Reitz and Trumble 2002a,b) and Japan (Abe and Tokumaru 2008). The results of the current study partially explain the roles that can be played by both host plants and parasitoids in the displacement of Liriomyza species.…”
Section: Sex Ratio Of D Isaeasupporting
confidence: 59%
“…Differential host plant use and differential effects of natural enemies have been suggested as contributing factors to displacement among Liriomyza species in the United States (Reitz and Trumble 2002a,b) and Japan (Abe and Tokumaru 2008). The results of the current study partially explain the roles that can be played by both host plants and parasitoids in the displacement of Liriomyza species.…”
Section: Sex Ratio Of D Isaeasupporting
confidence: 59%
“…The main reason for the displacement of L. sativae by L. trifolii in Hainan Island, China and California, USA, has been thought to be the lower susceptibility of L. trifolii populations to many commonly used insecticides [2], [3]. In contrast, Abe and Tokumaru [13] concluded that the reason for the displacement of L. trifolii by L. sativae in Kyoto Prefecture of Japan is the higher fecundity of L. sativae and differential effects of the local parasitoid complex on the two Liriomyza species. These mechanisms are likely to be mediated by other local environmental conditions, including temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes of invasions could include: (1) the replacement of one (or more) species by the newest invader (e.g. Reitz & Trumble 2002, Abe & Tokumaru 2008; (2) resistance to or exclusion of the newest invader by the established community of species (e.g. Elton 1958, Moulton & Pimm 1983, Robinson & Dickerson 1984, 1987, Case 1990, Drake 1990, Case 1991, Stachowicz et al 1999; or (3) niche shift or compression, in which species coexist but use less of their fundamental niche than they did prior to the latest invasion (e.g.…”
Section: Introductionmentioning
confidence: 99%